Plants and Phytomolecules for Immunomodulation Recent Trends and Advances - Sangwan, Neelam S.; Farag, Mohamed A.; Modolo, Luzia Valentina (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book describes the process of immunomodulation and the plants which possess immunomodulation properties to boost the immune system. The immunomodulation process is highly relevant to address emerging as well as existing diseases in humans. A better immune system triggers the cellular responses for neutralizing and combating the onset of disease conditions. Chapters in the book discuss plants that have profound effects on the health and well-being of humans. They discuss the natural phytochemicals that have immense diversity and uniqueness of molecules. Molecules belonging to phenylpropanoids, terpenoids, steroids, alkaloids, and tannins etc possess a variety of pharmacological activities. The chapters describe how bioactive exert effects even when taken as part of the diet, supplement, and or as traditional herbal medicine. This book provides up-to-date scientific knowledge about the activities and mechanisms and leads in the area of medicinal plants and phytochemicals with immunomodulation properties. This book is meant for students, academics, researchers, and industry professionals interested in pharmacology, immunology, and plant secondary metabolites.
Chapter 1. Immune system and mechanism of Immuno-modulation -- Chapter 2. Insights into the modulation of immune response, chemistry, and mechanisms of action of immuno-modulatory phytomolecules -- Chapter 3. Bioprospection and Clinical Investigations of Immunomodulatory Molecules -- Chapter 4. Pathway and genomics of immunomodulator natural products -- Chapter 5. Phytomolecules and metabolomics of immunomodulation - Recent Trends and Advances -- Chapter 6. Knowledge of African Traditional Medicine System: Immunomodulation -- Chapter 7. Middle Eastern diets as a potential source of immunomodulators -- Chapter 8. Immuno-Stimulant Properties of Some Commonly Used Indian Spices and Herbs with Special Reference to Region Specific Cuisines -- Chapter 9. Traditional Indian Knowledge of immunity from plants -- Chapter 10. Select Global Immune-Boosting Plants Used in Folklore Medicine -- Chapter 11. Immunomodulatory role of terpenoids and phytosteroids -- Chapter 12. Rhizomatous Plants - Curcuma longa and Zingiber officinale in affording immunity -- Chapter 13. Fruits as Boosters of Immune System -- Chapter 14. Solanaceous Plants for Immunomodulation -- Chapter 15. Food and vegetables as source of phytoactives for immunomodulation -- Chapter 16. Immunomodulation potential of woody plants -- Chapter 17. Biotechnological approaches for the production of immunomodulating phytomolecules -- Chapter 18. Technological mapping of plant-derived immunomodulator drugs: A patent-guided overview about species and its main compounds.
Keywords: Pharmacology; Immunology; Metabolism, Secondary; Plants; Botany; Pharmacology; Immunology; Plant Secondary Metabolism; Plant Science